VIEWS CORNERS AND THEIR ESTHETIC EFFECTS ON THE ARTISTICALLY SHAPE - Sanajlih, Owise Mahmood; Al-Haija, Suhair Salah Abu (European Scientific Journal, ESJ, 2013)
This study aims at exploring the views corners in Watching mural paints and painted grounds, as these corners are established from the line of the body plus the view line, and how we may observe different shapes. This study contains in to two searches: the murals paints and ground paints and how we may observe both of them and the impact of this view in the corner views and what result from constructing this shape beside what we may understand from them in ideas and covers. This study describes the mural paints and analyzes them artistically and aesthetic according to view of observing, then clarifying the relationship between observing the mural paint in right angle agreed with their real shapes and their facts, and observing the mural ground in acute angle agreed with their movable constructing rhythmic shapes even if their shapes are real and analyzed them in view and aesthetically. As this study discusses the relationship between the materiality, ideal and symbolic in observing the mural paints and ground paints in different angles. Adding this study clarifies the importance of arithmetic quantum for the aesthetic shapes to clarify that frequencies in the real shapes and geometrical shapes will gain them the same artistic and aesthetic characteristics.